Pengabdian Kepada Masyarakat Melalui Branding Wisata dalam Upaya Pengembangan Potensi Wisata Lembah Kecubung di Desa Penanggungan, Kabupaten Mojokerto - Sukma Ayu Susilowati; Mahimma Romadhona (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Village development activities are an integral part of the Merdeka Campus Competency Program (PKKM) in line with MBKM KKNT. Participating students perform community service as proof of their commitment to strengthening and supporting their community, in accordance with the principles of the Three Dharma Universities which include teaching, research, and devotion to the community. Village Development Program in Penangungan Village, Trawas, Mojokerto, attractive tourist destinations near the mountains, is a real step forward in providing ideas and solutions to the problems of the village community. The Trawas area is a famous tourist destination, with beautiful natural environments, cafes, and tourist attractions that contribute significantly to the village economy. Some destinations in Trawas, such as the Kecambung Valley, are newly opened on October 12, 2023, but may be missed as tourists tend to visit places that are widely discussed in the Trawas area. UPN DKV students focus Bina Village's work program on branding Agrowisata Valley Kecambung to increase the attractiveness and visibility of this new destination.